Polemik Frase “Duduklah di sebelah kanan-Ku” dalam Mazmur 110:1 - Ryan Renaldy Madunde (Jurnal Teologi dan Pelayanan Kerusso, 2023)
The book of Psalms, when viewed from a literary point of view, is grouped into a book with a poetic genre, so understanding every word in this book is certainly different when approaching a book with a narrative genre. It is this difficulty that needs to be considered in approaching books with the poetic genre, because this type of literature does not clearly state the background of the situation the author is experiencing when writing the message of God's Word. One of them is in Psalm 110:1 in the phrase "Sit at my right hand". If this phrase is not understood correctly it will indicate that there are two different and separate existences of God from one another, so this Psalm will be closely related to the study of systematic theology of Christology which refers to the person of the Lord Jesus Christ. If Jesus is meant in this verse then there will be LORD (YHWH) and Jesus sitting at the right hand of GOD. This study uses a qualitative method with a literature study which will exegetically discuss the phrase "Sit at My right hand", with an exegesis study approach the author hopes to find a meaning as close as possible to the meaning that the author of the book of Psalms wanted to convey, especially in chapter 110:1. ABSTRAK BAHASA INDONESIA Kitab Mazmur jika ditinjau dari segi sastranya dikelompokkan kedalam kitab dengan genre puisi, sehingga dalam memahami setiap kata dalam kitab ini tentulah berbeda ketika mendekati kitab dengan genre narasi. Kesulitan inilah yang perlu diperhatikan dalam mendekati kitab-kitab dengan genre puisi, sebab jenis sastra ini tidak mengemukakan secara gamblang tentang latar dari situasi yang sedang dialami penulis ketika menuliskan pesan Firman Tuhan tersebut. Salah satunya yang terjadi dalam Mazmur 110:1 pada frase “Duduklah di sebelah kanan-Ku”. Frase ini jika tidak dipahami dengan tepat akan mengindikasikan ada dua eksistensi Allah yang berbeda dan terpisah satu dengan yang lainnya, dengan begitu Mazmur ini akan berkaitan erat dengan studi teologi sistematika Kristologi yang merujuk kepada pribadi Tuhan Yesus Kristus. Jika Yesus yang dimaksudkan dalam ayat ini maka akan ada TUHAN (YHWH) dan Yesus yang duduk disebelah kanan TUHAN. Penelitian ini menggunakan metode kualitatif dengan studi literatur kepustakaan yang akan membahas secara eksegetikal frase “Duduklah di sebelah kanan-Ku”, dengan pendekatan studi eksegesis penulis berharap akan menemukan makna sedekat mungkin dengan makna yang ingin disampaikan penulis kitab Mazmur khususnya pada pasal 110:1.